1998
DOI: 10.1037/0022-3514.74.5.1238
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy as an interpersonal process: The importance of self-disclosure, partner disclosure, and perceived partner responsiveness in interpersonal exchanges.

Abstract: s (1988) interpersonal process model of intimacy suggests that both selfdisclosure and partner responsiveness contribute to the experience of intimacy in interactions. Two studies tested this model using an event-contingent diary methodology in which participants provided information immediately after their social interactions over 1 (Study I ) or 2 (Study 2) weeks. For each interaction, participants reported on their self-disclosures, partner disclosures, perceived partner responsiveness, and degree of intim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
825
3
21

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 919 publications
(907 citation statements)
references
References 30 publications
34
825
3
21
Order By: Relevance
“…The extent to which partners have the potential for mutual responsiveness to each other's needs, and the potential for close, intimate connection is an important marker of relationship quality (Maisel & Gable, 2009;Reis, Clark, & Holmes, 2004;Spielmann, MacDonald, & Tackett, 2012). Indeed, intimacy and closeness stemming from partner responsiveness are key to creating rewarding close relationships (Laurenceau, Feldman Barrett, & Pietromonaco, 1998;Laurenceau & Kleinman, 2006). A partner is considered responsive if s/he "attend[s] to and react [s] supportively to central, core defining features of the [partner's] self" (Reis et al, 2004, p. 203).…”
Section: Chapter 6 Settling For Less: Relationship Initiationmentioning
confidence: 99%
“…The extent to which partners have the potential for mutual responsiveness to each other's needs, and the potential for close, intimate connection is an important marker of relationship quality (Maisel & Gable, 2009;Reis, Clark, & Holmes, 2004;Spielmann, MacDonald, & Tackett, 2012). Indeed, intimacy and closeness stemming from partner responsiveness are key to creating rewarding close relationships (Laurenceau, Feldman Barrett, & Pietromonaco, 1998;Laurenceau & Kleinman, 2006). A partner is considered responsive if s/he "attend[s] to and react [s] supportively to central, core defining features of the [partner's] self" (Reis et al, 2004, p. 203).…”
Section: Chapter 6 Settling For Less: Relationship Initiationmentioning
confidence: 99%
“…That is, the speaker needs to perceive that the listener has understood the content of the individual's disclosure and, thus, believes that they are accepted and cared for. Laurenceau et al 118 expanded the interpersonal process model of intimacy to include perceived partner disclosure as well as self-disclosure. According to this model, both self-disclosures and partner disclosures contribute to the development of intimacy through the degree to which the speaker believes that their partner is responsive.…”
Section: Dyadic Level Theoriesmentioning
confidence: 99%
“…Although attachment may be amenable to change and can influence intimacy, it is viewed primarily as a dispositional characteristic, 127 whereas intimacy is viewed as amenable to change. 118 The primary outcome in our model is couplelevel psychologic and marital adaptation. We include marital adaptation along with distress in our conceptualization of couples' adaptation because a dyadic perspective is carried into all aspects of the relationship intimacy model.…”
Section: The Relationship Intimacy Model Of Couple Psychosocial Adaptmentioning
confidence: 99%
“…It has been suggested that when couple members communicate openly with each other and express their personal feelings, they perceive each other as responsive and understanding, which in turn enhances couples' intimacy and relationship satisfaction (Laurenceau, Barrett, & Pietromonaco, 1998;Reis & Shaver, 1988). This implies that a support behavior such as active engagement, which includes open communication, will be positively associated with relationship satisfaction.…”
mentioning
confidence: 99%